Strategies for evaluation : forming judgments about information for classroom, homework, and test success - Wilson, David, 1974- 4 0 16; 5 (New York : Rosen Central, 2006)
Introduces a number of strategies designed to help in evaluating information for use in class preparation, homework, and written exams.
Includes bibliographical references (p. 43-45) and index.
Wilson's Junior High School;School Library Journal
6.2;5-8;5-8
Keywords: 2 -- 0; 6; Study and teaching;Study and teaching -- Critical thinking;Evaluation;Critical thinking.;Evaluation.;Critical thinking.;Evaluation. -- Juvenile literature.;Juvenile literature; 20; 2